Enterprise hubs as a mechanism for local economic development in rural areas. (July 2022) - Merrell, Ian; Phillipson, Jeremy; Gorton, Matthew; Cowie, Paul
Abstract: Until recently, rural areas have been largely disregarded in innovation policies, due to the lack of physical proximity between businesses required to create agglomeration benefits. Rural enterprise hubs – defined as physical infrastructure that provides workspaces to multiple tenant businesses, with additional services such as shared equipment, meeting rooms, co-working spaces, and business advice or support - are one means of increasing not only physical, but a wide range of non-spatial proximities between rural businesses. Drawing on and extending proximity theory, and based on qualitative case study research, this paper provides the first in-depth analysis of how co-location of businesses within Rural Enterprise Hubs can generate benefits for tenants and overcome a lack of proximity to networks and support systems. It identifies the salience of these benefits for different types of businesses and the extent to which hubs help to overcome common constraints faced by rural businesses. Highlights: Hubs provide eight beneficial proximities to tenants, beyond geographic proximity. Market and professional proximity are highly relevant for rural micro-businesses. Separation from home is important for previously homebased tenants. Rural hubs can help to overcome social, institutional and geographic barriers.